Satellite tracking of red-listed nominate lesser black-backed gulls (Larus f. fuscus): Habitat specialisation in foraging movements raises novel conservation needs - Risto Juvaste; Elena Arriero; Anna Gagliardo; Richard Holland; Markku J. Huttunen; Inge Mueller; Kasper Thorup; Martin Wikelski; Juhani Hannila; Maija-Liisa Penttinen; Ralf Wistbacka (ELSEVIER SCIENCE BV, 2022)
In contrast to many other gull species, nominate lesser black-backed gulls (Larus fuscus fuscus, nLBBG) have shown generally decreasing population trends throughout their breeding area in northern and eastern Fennoscandia over the past decades and are now red-listed. Interspecific competition, predation, increased disturbance, organochlorine poisoning and food shortages were suggested as main reasons for the overall decrease. Here we contribute to a better understanding of population declines by comparing foraging movements of satellite tracked adult gulls in three geographical areas of Finland (West, South, and East) that differ in their population trends. Our analysis examines potential differences and preferences in the feeding site behaviour of adult gulls. Our comparison of the three geographical areas showed that nLBBGs preferred feeding at fur farms in West Finland, waste dumps in South Finland, and lakes and fields in East Finland. We found individual gulls of this purportedly generalist species to be highly specialised in their foraging behaviour, particularly those that might be associated with their survival probabilities. We hypothesise that differences in foraging behaviour and food availability during the breeding season are partially responsible for differences in demographic trends between populations. Specifically, we identify potential local conservation problems such as shooting in birds visiting fur farms. Our data suggest that the effective conservation and management of endangered nLBBGs could be aided by simple actions in the breeding areas in addition to better protection throughout the annual movement cycle. (C) 2017 The Authors. Published by Elsevier B.V.